2021
DOI: 10.11648/j.ijimse.20210601.13
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization of Super White Washed Stretch Denim Fabric by Deviating Washing Process Time and Machine RPM

Abstract: Over the last few decades, a lot of innovations and development works had already made denim "classic" in the fashion cycle. The modern consumers of today's world are not only devoting themselves on clothing comfort but also emphasizing on economic and environmental sustainability. As a result, there has been increasing interests in terms of using environment friendly, non-toxic and biodegradable wet process such as super white wash. Though it enlarged higher consumer aspects and market opportunities in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…That's why, the RMG experts and prominent economists suggested that both product and market diversification is a must for the existence of the economy, if the country wants to explore its current lead in global apparel export, just after post pandemic situation. Bangladesh depends on five items such as men's and women's t-shirt, trouser, shirt, jacket and sweater for export while Vietnam has diversified its product line (Rahaman et al, 2021b;Hasan et al, 2021). Only in a single market, Vietnam exports 10 types of products in USA, including women's knit shirts and blouses (MMF), women's trousers (cotton), women's knit shirts and blouses (cotton), women's trousers (MMF), men's knit shirts (cotton), dresses (MMF), men's trousers (MMF), men's knit shirts (MMF), men's trousers (cotton), and women's coats (MMF).…”
Section: Product and Market Diversificationmentioning
confidence: 99%
“…That's why, the RMG experts and prominent economists suggested that both product and market diversification is a must for the existence of the economy, if the country wants to explore its current lead in global apparel export, just after post pandemic situation. Bangladesh depends on five items such as men's and women's t-shirt, trouser, shirt, jacket and sweater for export while Vietnam has diversified its product line (Rahaman et al, 2021b;Hasan et al, 2021). Only in a single market, Vietnam exports 10 types of products in USA, including women's knit shirts and blouses (MMF), women's trousers (cotton), women's knit shirts and blouses (cotton), women's trousers (MMF), men's knit shirts (cotton), dresses (MMF), men's trousers (MMF), men's knit shirts (MMF), men's trousers (cotton), and women's coats (MMF).…”
Section: Product and Market Diversificationmentioning
confidence: 99%